Increased motivation for physical training of pupils of 5-6 classes - Alfiya Deyneko (Kharkiv State Academy of Physical Culture, 2014)
Purpose: to analyze the impact of experimental techniques to motivate pupils of 5-6 classes in physical training at school. Material and methods: student motivation to physical training was determined by means of two questionnaires conducted before and after the implementation of the methodology in the control and experimental groups. 109 students 5-6 grade Kharkiv secondary school № 67 were selected: 5-A and 6-A forms was the experimental group, 5-B and 6-B forms formed the control group. Results: a low level of student interest in physical training and the importance of coercion in attendance on a background of diverse sports entertainment adolescents is revealed. Conclusions: positive influence of methodology as on the level of interests, values and motivations, and pupils behavior is observed.